BEAR WITNESS: Dua Wacana Tentang Kesaksian Dan Kebenaran - Karen Campbell Nelson (Institut Filsafat dan Teknologi Kreatif Ledalero, 2015)
The meaning of testimony and truth play an important role in both a legal/judicial discourse and a religious, particularly Christian discourse. I trace the history of testimony in legal discourse, beginning with the Hammurabi Code and its influence on ancient legal codes of Mesopotamia, including that found in the Pentateuch and continue with a discussion of multiple meanings of testimony in Augustine and French philosopher, Paul Ricœur that begin to lay the groundwork for bridging the two discourses. Contributions from feminist theology, particularly the validation of women’s experience as a source of theology, the role of immanence, and the shift from understandings of power as “power over” to “power with” as well as a transitional justice framework help make the case for dialog between these two discourses so they can enhance and strengthen each other. I include in sections of the article my own narrative to accent the theme of testimony. Keywords: Kesaksian, kebenaran, konteks hukum, pengadilan, konteks iman, hermeneutik.